O lúdico na garantia dos direitos de aprendizagem e desenvolvimento da criança: um estudo na pré-escola do Centro de Educação Infantil de Benjamin Constant-Am - Mangabeira, Rosangela Hilário (Brasil, 2023)
This course conclusion work had as main objective to verify if the ways of using ludicity in early childhood education have been guaranteeing the fulfillment of children's learning and development rights in the context of a preschool class of a CMEI in the municipality of Benjamin Constant . For this, it became necessary to know the concept of ludicity and its importance in children's learning from the conception of early childhood education teachers; identify recreational activities and the ways in which they are developed in the different educational spaces of the school; describe the school's physical and material infrastructure for the use of playfulness in the educational environment; and verify how the rights of learning and development are being guaranteed based on the ludic activities developed. For the development of the monograph, readings were carried out in the works of Maluf (2003), Santos (2009), Bruner (1983), Kishimoto (2017), Ishida (2011), among others that deal with the importance of playfulness in early childhood education, and in legal documents such as RCEI (1998), BNCC (2018), LDB (1996), ECA (1990) and DCNEI (2009). The research was carried out at the Frei Benigno Falchi Educational Creche Municipal with three (3) Pre-II kindergarten teachers. The research was constituted as a field research of qualitative methodology, making use of a questionnaire and participatory observation to verify if the ludic is present in the day-to-day of the preschool child and how it is being used to guarantee the children's learning and development rights. It was noticed that the ludic in preschool is carried out from jokes, games, songs, and dances, these dynamic and creative activities for the motivation and interest of the children that lead them to build knowledge in a relaxed and pleasant way, considering their learning and development rights. Therefore, it was found that with the appreciation of work with games and games, teachers will have an indispensable tool for the daily work in the learning of their students and that the ludic activities developed with the children favored imagination, attention, participation, exploration, conviviality, sharing, among other fundamental aspects to guarantee the child's learning and development rights, becoming a very important tool to develop the child physically, socially, emotionally and cognitively.